Anisotropic magnetized tubular microrobots for bioinspired adaptive locomotion. (June 2022) - Yan, Guanghui; Xu, Borui; Shi, Xiaojie; Zong, Yang; Wu, Yue; Liu, Jinrun; Ouyang, Yi; Chen, Guoxiang; Cui, Jizhai; Mei, Yongfeng
Highlights: A tubular microrobot prepared by rolled-up nanotechnology performs rolling and tumbling motion analogous to Escherichia coli . A motion switching from rolling to tumbling occurs for the tubular microrobot by adjusting the frequency of rotating magnetic field. The net locomotion of tubular microrobot near substrate comes from the competition of fluidic friction and pressure, and the motion switching depends on the magnetized statuses and discrepancy of drag force. The motion switch endows the microrobot with the capability of adaptive locomotion to cross obstacles and microfluidic manipulation to delivery cargo by tuning local microvortex. Abstract: Mimicry of motile microorganisms offers new concepts and strategies to design and manipulate microrobots. As a representative instance, Escherichia coli switches its motility between swimming and tumbling to adapt to surroundings. Inspired by this, we present a tubular microrobot behaving rolling and tumbling motion modes analogous to the motion of Escherichia coli, as a result of the anisotropic magnetized status with radially magnetized status at rolling and longitudinally magnetized one at tumbling. The motion behavior of microrobot as rolling or tumbling is determined by the frequency of rotating magnetic field. The threshold frequency for switching is closely related to the amplitude of magnetic field, viscosity of solution and size of microrobot. The net locomotion near substrate comes from the friction and pressure, and the motion switching is due to the magnetized statuses and discrepancy of drag force. The switch from rolling to tumbling endows the microrobot with adaptive locomotion to cross obstacles. Furthermore, microfluidic manipulation through rotational microrobot is achieved based on the local microvortex, which is generated from the hydrodynamic interaction between microrobot and substrate. This manipulation is applied in cargo delivery and release by altering surrounding microfluid via switchable motion modes. This work opens up new possibilities in improving moving ability and extending functions of microrobots through bioinspired motion behaviors. Graphical abstract: Image, graphical abstract